2017
DOI: 10.1021/acs.nanolett.7b03918
|View full text |Cite
|
Sign up to set email alerts
|

A New Cell Separation Method Based on Antibody-Immobilized Nanoneedle Arrays for the Detection of Intracellular Markers

Abstract: Focusing on intracellular targets, we propose a new cell separation technique based on a nanoneedle array (NNA) device, which allows simultaneous insertion of multiple needles into multiple cells. The device is designed to target and lift ("fish") individual cells from a mixed population of cells on a substrate using an antibody-functionalized NNA. The mechanics underlying this approach were validated by force analysis using an atomic force microscope. Accurate high-throughput separation was achieved using one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Kawamura et al have demonstrated a unique form of cell capture and sorting using antibody‐functionalized silicon nanoneedle arrays . They interfaced cocultures of two different cell types using nanoneedle arrays.…”
Section: Biochemical Sensingmentioning
confidence: 99%
“…Kawamura et al have demonstrated a unique form of cell capture and sorting using antibody‐functionalized silicon nanoneedle arrays . They interfaced cocultures of two different cell types using nanoneedle arrays.…”
Section: Biochemical Sensingmentioning
confidence: 99%
“…In addition to advancements in delivery, several sampling devices equipped with nanoneedle arrays were established for monitoring intracellular activity under the assistance of steerable forces supported by simple pressing or micromanipulators. [ 53,150 ] Using their diamond nanoneedle platform, Wang et al accomplished in situ probing of specific intracellular signaling elements involving in cellular innate immunity after the stimulator of interferon genes (STING) pathway was activated by nanoneedle‐mediated delivery of double‐stranded DNAs (Figure 7c). [ 149 ] After the aptamer‐modified diamond nanoneedles were inserted into the cytoplasmic domain by centrifugation, the surface bound aptamer molecules could specifically recognize the target biomolecules of interest (such as the transcription factor NF‐κB) in the cytosol.…”
Section: Assisted Penetrationmentioning
confidence: 99%
“…By a similar strategy, antibody-functionalized nanoneedle array was fabricated to target individual cells, and separate them from a mixed population of cells on a substrate (Kawamura et al, 2017). The nanoneedle array comprised of 10,000 nanoneedles was fabricated using top-down MEMS (Micro-Electro-Mechanical System) technique with each nanoneedle <200 nm diameter and more than 20 µm long.…”
Section: Nanoneedle For Single-cell Samplingmentioning
confidence: 99%